2008
DOI: 10.29333/ejgm/82597
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde-Induced Damage in Lungs and Effects of Caffeic Acid Phenethyl Ester: A Light Microscopic Study

Abstract: Aim:The aim of this study was to investigate the toxicity of formaldehyde on lung and protective effects of caffeic acid phenethyl ester against these toxic effects.Methods: For this purpose, 21 male Wistar rats were divided into three groups. The rats in Group I comprised the controls, while the rats in Group II were injected with formaldehyde (FA). The rats in Group III received CAPE daily while exposed to formaldehyde. After the treatment, lungs tissues were evaluated by microscopic examination. Results:In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…This was also supported by Turkoglu et al (2008) who suggested that respiratory and transitional epithelium of nasal mucosa was more susceptible to formaldehyde damage than other epithelium. The cellular disorganization and hyperchromatic nuclei of respiratory mucosa in rabbits was identical to the findings of Javedan and Entezarizaher (1999) in rat nasal mucosa exposed to 2 and 5 ppm of formaldehyde.…”
Section: Discussionsupporting
confidence: 54%
“…This was also supported by Turkoglu et al (2008) who suggested that respiratory and transitional epithelium of nasal mucosa was more susceptible to formaldehyde damage than other epithelium. The cellular disorganization and hyperchromatic nuclei of respiratory mucosa in rabbits was identical to the findings of Javedan and Entezarizaher (1999) in rat nasal mucosa exposed to 2 and 5 ppm of formaldehyde.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, impaired antioxidant activities of enzymes, in metabolic detoxification of oxidative by-products have been also reported in experimental animals treated with FA (22, 46). Finally, FA exposure can lead to inflammation and to a consequent excess of oxidative stress (47). Activated macrophages and neutrophils can release ROS, such as hydrogen peroxide and hypochlorite acid, that can induce LPO and MDA formation.…”
Section: Discussionmentioning
confidence: 99%